Investigation on hourly and monthly thermal comfort in the humid tropics of Malaysia - Harimi Djamila; Ming, Chu Chi; Sivakumar Kumaresan (MDPI, 2015)
Investigations on hourly and monthly indoor neutral temperature variations in the humid tropics are limited in literature. In Malaysia, the variation of hourly outdoor mean temperature is slightly higher than the monthly mean temperature. Consequently, this leads to the hypothesis that the variation of hourly neutral temperatures might be higher than the monthly neutral temperatures. Understanding the impact of hourly and monthly temperature variation on thermal comfort will certainly provide the design direction of future indoor environments. In this study, extensive measurements from residential buildings were used to investigate the observed variation. Linear regression and Griffiths methods were explored for analyzing the results. There was almost no variation on hourly and monthly neutral temperatures within the range under study. Further research is highly recommended due to the limited data collection and the limitations of the employed methods. It is highly advised to further investigate the hourly temperature variation on thermal comfort during nighttime and early morning. This is for an accurate interpretation of the results.